SPECTRAL DECOMPOSITION OF A FIRST ORDER FUNCTIONAL DIFFERENTIAL OPERATOR - A.Sh. Shaldanbayev; M.B. Ivanova; A.N.Urmatova; A.A. Shaldanbayeva (Academic Scientific Journal of Computer Science, 2019)
In this paper we study spectral properties of a boundary value problem of a first-order differential equation with constant coefficients and a deviating argument. By spectral properties we mean completeness and basis property of the system of eigenfunctions and associated functions of the boundary value problem, as well as the Volterra property.